A Self‐Ordered Nanostructured Transparent Electrode of High Structural Quality and Corresponding Functional Performance. Issue 20 (4th April 2021) - Döhler, Dirk; Triana, Andrés; Büttner, Pascal; Scheler, Florian; Goerlitzer, Eric S.A.; Harrer, Johannes; Vasileva, Anna; Metwalli, Ezzeldin; Gruber, Wolfgang; Unruh, Tobias; Manshina, Alina; Vogel, Nicolas; et al.
Abstract: The preparation of a highly ordered nanostructured transparent electrode based on a combination of nanosphere lithography and anodization is presented. The size of perfectly ordered pore domains is improved by an order of magnitude with respect to the state of the art. The concomitantly reduced density of defect pores increases the fraction of pores that are in good electrical contact with the underlying transparent conductive substrate. This improvement in structural quality translates directly and linearly into an improved performance of energy conversion devices built from such electrodes in a linear manner. Abstract : Highly ordered nanoporous transparent electrodes fabricated via nanosphere lithography and anodization is presented. Perfect hexagonal order over domains of thousands of square micrometer is acheived using self‐assembly methods exclusively. Solar cells made from them reach significantly improve performance compared to their disordered counterparts.